The first karyotype study in palpigrades, a primitive order of arachnids (Arachnida: Palpigradi) - Král, Jirí; Kovác, L'ubomír; St'áhlavský, Frantisek; Lonský, Petr; L'uptácik, Peter (Genetica, 2008)
Chromosomes of palpigrades (Arachnida: Palpigradi), a rare arachnid order with numerous primitive characters, were studied for the first time. We analysed two species of the genus Eukoenenia, namely E. spelaea and E. mirabilis. Their karyotypes are uniform, consisting of a low number of tiny chromosomes that decrease gradually in size. Study of the palpigrade karyotype did not reveal morphologically differentiated sex chromosomes. Analysis of E. spelaea showed that constitutive heterochromatin is scarce, GC-rich, and restricted mostly to presumed centromeric regions. Meiosis is remarkable for the presence of a short diffuse stage and prominent nucleolar activity. During prophase I, nuclei contain a large nucleolus. Prominent knob at the end of one bivalent formed by constitutive heterochromatin is associated to the nucleolus by an adjacent NOR. Presence of a nucleolus-like body at male prophase II suggests activity of NOR also during beginning of the second meiotic division. The data suggest acrocentric morphology of palpigrade chromosomes. Palpigrades do not display holocentric chromosomes which appear to be apomorphic features of a number of arachnid groups. These are: acariform mites, buthid scorpions, and spiders of the superfamily Dysderoidea. Therefore, cytogenetic data do not support a close relationship of palpigrades and acariform mites as suggested previously.
Keywords: Animals; Female; Meiosis; biologická evoluce; karyotypizace; ženské pohlaví; meióza; druhová specificita; Karyotyping; Species Specificity; Mitosis; mitóza; pavoukovci; pohlavní chromozomy; Arachnida; Chromosomes; Male; Sex Chromosomes; zvířata; mužské pohlaví; Biological Evolution; chromozomy